(untitled) - Desborough, John (Indianapolis, Ind., 1996)
<Intranet> concepts and Architecture - server; Intranet concepts and Architecture - Client; Application Building blocks. Contructing information resources additional information servers appendices (samples, case study, server products, CD ROM )
Keywords: Intranets (Computer networks),Mạng nội bộ (Mạng máy tính)